ACADEMIC LIFE OF THE PHILOSOPHER: PROFESSOR OLEKSANDR OLEKSANDROVICH MAMALUY (29. 07. 1939 - 06. 12. 2023) - Karpenko , Ivan; Perepelytsia , Oleh (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2024)
The article is dedicated to highlighting the creative path of the professor of V. N. Karazin Kharkiv National University, editor-in-chief of The Journal of V. N. Karazin Kharkiv National University Series “Philosophy. Philosophical Peripeteias” (1992-2017) O. O. Mamaluy. The personality of O. O. Mamaluy as a university professor, scientist, head of the department, scientific director of scientific research is revealed. His personal contribution to the organizational and educational development of university academic philosophy and philosophy at the university is noted. His vision of the mission of the university in society, understanding of the specifics of philosophy and the peculiarities of its teaching at the university are revealed. Emphasis is placed on the relationship between university education and philosophy, which ensures fundamentality, integrity, openness, humanity, free creative spirit, criticality, and democracy. The scientific achievements are characterized, the directions of philosophical thinking, the key concepts of the philosophy of O. O. Mamaluy are determined. In particular, the significance of the conceptualization of contemporarity as a state of post(non-pre)modernity, when the prefix "non-pre" is interpreted as a "way of concretizing" the state of "post", in particular in the context of Ukrainian society, is determined. The problem of authorship, the conceptualization of "authorship (trans)discursivity" and especially the problem of freedom, which is considered in a specific historical context and is inseparable from specific practices of emancipation, are defined as the leading themes of O. O. Mamaluy's philosophizing. The need to form an image of philosophy as a personal, authorial, existential philosophizing is also noted, which together appears as a dialogue with the world philosophical tradition and is carried out as a creative co-philosophizing.